2020
DOI: 10.1016/j.jmoldx.2020.02.012
|View full text |Cite|
|
Sign up to set email alerts
|

Detailed Molecular and Immune Marker Profiling of Archival Prostate Cancer Samples Reveals an Inverse Association between TMPRSS2:ERG Fusion Status and Immune Cell Infiltration

Abstract: Prostate cancer is a major global health issue and the second most common cause of cancer death in males in the developing world. 1 Better methods for patient stratification are urgently needed.Our understanding of the molecular pathology of prostate cancer is evolving fast, with advances in sequencing methods and bioinformatics. The Cancer Genome Atlas performed detailed molecular analysis on 333 primary prostate J.R. and C.V. contributed equally to this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…However, there are mixed findings regarding the presence of inflammation by the ERG-defined subtype. An inverse association between TMPRSS2-ERG fusion and TILs was identified by integrating an image analysis with RNA sequencing in 27 archival radical prostatectomy cases [76]. In contrast, Burdova et al found that CD204+ macrophages and CD3+ T-lymphocytes may infiltrate the tumor region more intensely in TMPRSS2-ERG fusion-positive cases, compared to fusion-negative cases [77], in line with findings from Kaur and colleagues, showing increased T-cell density in ERGpositive tumors [78].…”
Section: Heterogeneity Among Immune Phenotypessupporting
confidence: 52%
“…However, there are mixed findings regarding the presence of inflammation by the ERG-defined subtype. An inverse association between TMPRSS2-ERG fusion and TILs was identified by integrating an image analysis with RNA sequencing in 27 archival radical prostatectomy cases [76]. In contrast, Burdova et al found that CD204+ macrophages and CD3+ T-lymphocytes may infiltrate the tumor region more intensely in TMPRSS2-ERG fusion-positive cases, compared to fusion-negative cases [77], in line with findings from Kaur and colleagues, showing increased T-cell density in ERGpositive tumors [78].…”
Section: Heterogeneity Among Immune Phenotypessupporting
confidence: 52%
“…Whether the presence/type of immune cells serves as the driving force for fusion‐driven PCa or whether the fusion‐state is responsible for the influx of immune cells in the prostate tumor microenvironment warrants further investigation, which is beyond the scope of the present study. It is intriguing that previously published studies investigating the association between immune cell infiltration and presence of TMPRSS2‐ERG fusion in clinical samples have reported either a positive relationship 55 between increased prostate inflammation and TMPRSS2‐ERG fusion or inverse relationship 56 between the two. Nevertheless, the strong presence of immune cells in the fusion‐driven PCa is one remarkable and novel observation from the present study that cannot be overlooked; it has the potential to serve as a potential indicator of fusion‐driven PCa and could very well serve as a target for future therapies specific against fusion‐driven PCa.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that the Tmprss2-Erg fusion promotes recruitment of regulatory T cells to the tumor site [50]. Recent studies have shown an association between low levels of TILs comparing TMPRSS2-ERG fusions producing chimeric transcripts in the coding in the fusion-positive cases results in suppression of immune response by alteration of cytokine production [51,52].…”
Section: Phosphatase and Tensin Homologue (Pten)mentioning
confidence: 97%